EFFECT OF LIQUID NITROGEN FREEZING AND SUBSEQUENT STORAGE ON SURVIVAL OF STAPHYLOCOCCUS AUREUS AND STREPTOCOCCUS PYOGENES IN TREATED PRAWN MEAT - CHAKRABARTI, R; CHOUDHURY, D R (Fishery Technology, 2017)
Prawn meat treated with Streptococcus pyogenes B-49-2 culture and Staphylococcus aureus ATCC-12598- culture were frozen in conventional plate freezer at -40Â°C and by spray type liquid nitrogen freezer. The frozen products were stored at -18Â°C. Streptococcus pyogenes B-49-2 showed low sensitivity to cold injury during freezing and frozen storage. Staphylococcus aureus ATCC-12598 survived during the entire storageperiod of 240 days. Total bacterial count of untreated prawn meat was found to be always lesser in liquid nitrogen frozen products than that in plate frozen products.